2017
DOI: 10.17267/2238-2704rpf.v7i1.1230
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Exercise in Patients After Cardiac Transplantation: A Systematic Review

Abstract: | Objective:To synthesize the main scientific evidences related to the effects of different protocols of therapy by exercise in patients submitted to cardiac transplantation. Methodology: The research was carried out from the databases MEDLINE and EMBASE via Ovid from 2000 until October 1, 2016, the accumulated index of the literature for nurses and other health professionals (CINAHL), LILACS and Cochrane Central of controlled studies), using the descriptors: heart transplantation, exercise, physiotherapy, phy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 9 publications
(9 reference statements)
1
3
0
Order By: Relevance
“…Our meta‐analysis showed an overall improvement in exercise capacity (VO 2 peak) in SOT recipients as did Didsbury et a l. [17]. Other reviews have shown improvements in VO 2 peak in several single organ groups [11‐16,20,55], but none of them conducted meta‐analyses including liver and lung transplant recipients. Low VO 2 peak has been associated with higher risk for cardiovascular disease and is a predictor of mortality in chronic disease populations [8] and SOT recipients [1] so an improvement in VO 2 peak may improve prognosis and reduce risk for cardiovascular disease post‐transplant.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Our meta‐analysis showed an overall improvement in exercise capacity (VO 2 peak) in SOT recipients as did Didsbury et a l. [17]. Other reviews have shown improvements in VO 2 peak in several single organ groups [11‐16,20,55], but none of them conducted meta‐analyses including liver and lung transplant recipients. Low VO 2 peak has been associated with higher risk for cardiovascular disease and is a predictor of mortality in chronic disease populations [8] and SOT recipients [1] so an improvement in VO 2 peak may improve prognosis and reduce risk for cardiovascular disease post‐transplant.…”
Section: Discussionsupporting
confidence: 68%
“…Another strength is the novel contributions of our study compared to previous reviews. Prior reviews were conducted on recipients of a single transplant type (i.e., organ specific) and included a smaller number of studies [11][12][13][14][15][16]20,55] preventing the pooling of results or were focused on a narrower list of outcome measures [56]. We have included 20 new studies [26,[28][29][30][31][32][33][34][35][36][38][39][40][41]43,48,50,[52][53][54] not included in Didsbury's review [17].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations